Study of Belat Fishing Gear in the Waters of Dumai, Riau Province - Asna, Laena; Bustari, Bustari; Yani, Alit Hindri (Journal of Coastal and Ocean Sciences, 2023)
Based on data from the Dumai City PPI Office in 2013 and 2019, the number of belat fishing gear in Dumai City has decreased from 20 to 7. It is suspected that there are symptoms of overfishing caused by the non-selectivity of this belat, where the bycatch is greater than the main catch, and supported by belat construction data because it is known that fishermen use a small mesh size of 1 inch. The study's purpose is to find out how the main catch and bycatch which amount of catch is more caught. Data analysis using descriptive analysis and research methods with survey methods. The main catch of belat weighing 1.914.9 kg is composed of white shrimp (Penaeus indicus), kelong shrimp (Penaeus merguiensis), Malaysian prawn (Macrobranchium rosenbergii), smallhead catfish (Euristhmus microceps), bluespot mullet (Crenimugil seheli), gulamah (Panna microdon), and the bycatch weighs 710 kg is composed of Fourfinger threadfin (Eleutheronema tetradactylum), sagor catfish (Hexanematichthys sagor), milk shark (Rhizoprionodon acutus), stingray (Dasyatis sephen), silver sillago (Sillago sihama), white snapper (Lates calcarifer), spotted scat (Scatophagus argus), crab (Portunus pelagicus), pomfret (Pampus argenteus), and saddle grunt (Pomadasis maculates).